Yield and chemical composition of the essential oil of species of the Asteraceae family from Atlantic Forest, South of Brazil. Issue 4 (4th July 2018) - do Amaral, Wanderlei; Deschamps, Cícero; Biasi, Luiz Antonio; Bizzo, Humberto R.; Machado, Marília Pereira; da Silva, Luiz Everson
Abstract: The essential oil yield and composition of 17 species of the Asteraceae family were evaluated. Samples were obtained by hydrodistillation of the leaves and inflorescences and they were analyzed by GC-MS and GC-FID. A total of 13 species presented essential oils with yields ranging from 0.06 to 3.36% in fresh samples and from 0.07 to 2.53% in dried samples. Erechtites valerianifolius (Wolf) DC. produced the highest essential oil yield from both fresh and dried samples. Seventy-nine constituents were identified in essential oils from Asteraceae species, mainly consisting of monoterpenes and sesquiterpenes.